Acetylcholinesterase activity and menstrual remissions in myasthenia gravis. - Vijayan, N (1977)
Menstrually related temporary remissions of myasthenic symptoms are reported to occur in 25 to 50% of female patients. Even though this has been attributed to hormonal changes associated with the menstrual cycle the underlying mechanism of this hormonal influence has remained elusive. The present study demonstrated a cyclical variation in the activity of red cell acetylcholinesterase (EC 3.1.1.7) enzyme (AChE) with a marked reduction at the time of menstrual remission of symptoms of myasthenia. These cyclical changes were abolished by thymectomy. It appears, therefore, that menstrual remission in myasthenia is at least partly due to hormone-induced changes in AChE activity. This process seems to be under the control of the thymus gland.